STUDI KORELASI KETERPAPARAN MEDIA DAN PENGARUH TEMAN SEBAYA TERHADAP PERILAKU SEKSUAL BERISIKO PADA REMAJA - Situmeang, Lamria; Novika, Revi Gama Hatta; Nurjanah, Nourma; Mauludiyah, Zaida; Rahmah, Lestari (Lembaga Penelitian dan Penerbitan Hasil Penelitian Ensiklopedia, 2024)
Abstract: High school students are categorized as adolescents aged 15 to 18 years and are very vulnerable to adolescents committing sexual deviations if they do not get enough knowledge about sex. This problem is overcome by providing sexual education carried out by various parties such as parents, government, educational institutions, and so on. The problem of this study is whether there is a relationship between the level of knowledge, media exposure, peers with risky sexual behavior in adolescents of SMA N 6 Jambi City. The purpose of the study was to determine the correlation of media exposure and peer influence on risky sexual behavior in adolescents. This research is a study that uses a quantitative approach with the type of analytical observation research that is to find the relationship between variables. This study uses a cross sectional approach which aims to get a relationship by studying the dynamics of the correlation between the independent variable and the dependent variable that occurs in the object of research measured or collected simultaneously (simultaneously). The results showed a relationship between media exposure (p value: 0.001) and peer influence (p value: 0.038) on risky sexual behavior in adolescents. It is recommended for adolescents, especially SMA N 6 Jambi City, to protect themselves and learn about Sex Education well in order to avoid problems of risky sexual behavior. Students of SMA N 6 Jambi City can do this.Keywords: Teens, Media, Peers